The first record of the genus Eskemukerjea (Polygonaceae) from China - Gou, Yu-Ting; Zhu, Zhen-Hua; Zhou, Xin-Xin; Chen, Yong-Jun; Li, Bo (Phytotaxa, 2022)
Eskemukerjea is a monotypic genus containing the endemic nepali E. megacarpum. Based on examination of herbarium specimens (including types), consultation of protologues and other relevant literature, as well as investigation of the newly discovered populations in Chinese Tibet, we here record E. megacarpum for the first time out of Nepal. An updated morphological description, original field photographs, and a distribution map are provided.